2005
DOI: 10.1038/sj.bjc.6602541
|View full text |Cite
|
Sign up to set email alerts
|

Long-term protective effect of high-risk human papillomavirus testing in population-based cervical screening

Abstract: We prospectively evaluated the 5-year predictive values of adding high-risk human papillomavirus (hrHPV) testing to cytology for the detection of Xcervical intraepithelial neoplasia (CIN)3 lesions in a population-based cohort of 2810 women. At baseline, nine (0.3%) women had prevalent lesions XCIN3, all being hrHPV positive. After 5 years of follow-up, four (6.5%) of the 62 hrHPV-positive women with normal cytology developed lesions XCIN3, vs only one (0.05%) of the 2175 hrHPV-negative women with normal cytolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 12 publications
(10 reference statements)
4
36
0
4
Order By: Relevance
“…In their 5-year cohort study in The Netherlands of 2810 women aged 30 -60 years with normal cytology, Bulkmans et al (2005) show that, in agreement with previous findings from the US (Sherman et al, 2003), France (Clavel et al, 2004) and the UK (Cuzick et al, 2003;Peto et al, 2004), HR HPV testing combined with cytology has higher sensitivity and higher negative predictive value for cervical intraepithelial neoplasia (CIN) 3 and cancer than cytology alone. Specificity was, however, slightly lower for HPV testing and cytology (93%) than cytology alone (95%).…”
supporting
confidence: 75%
See 3 more Smart Citations
“…In their 5-year cohort study in The Netherlands of 2810 women aged 30 -60 years with normal cytology, Bulkmans et al (2005) show that, in agreement with previous findings from the US (Sherman et al, 2003), France (Clavel et al, 2004) and the UK (Cuzick et al, 2003;Peto et al, 2004), HR HPV testing combined with cytology has higher sensitivity and higher negative predictive value for cervical intraepithelial neoplasia (CIN) 3 and cancer than cytology alone. Specificity was, however, slightly lower for HPV testing and cytology (93%) than cytology alone (95%).…”
supporting
confidence: 75%
“…The improvement in sensitivity and negative predictive value made possible by the addition of HR HPV testing to cytology supports the use of viral testing in order to increase the screening interval, although the findings of Bulkmans et al (2005) should be interpreted with some caution as their study was relatively small, and, as the authors emphasise, an increased sensitivity is implicit in performing any additional test (Franco and Ferenczy, 1999).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Large longitudinal studies have shown that screening can be improved by the introduction of a hrHPV test as a primary screening tool [14][15][16][17][18][19][20][21][22][23][24][25][26]. Compared to primary screening with Pap cytology, a primary hrHPV test has a superior sensitivity for cervical cancer [24] and its high-grade precursor lesions (cervical intraepithelial neoplasia grade 3, CIN3) [14][15][16][17][18][19][20][21]26].…”
Section: Introductionmentioning
confidence: 99%